Video surveillance and security system. - Ramli, Abdul Rahman; Koay, Au Yeong; Lew, Yuan Pok (2004)

(untitled)
The present invention relates to video surveillance and security systems (10), incorporates with a program to "detect", capture and save motion image, to monitor or capture events happened at a selected area, especially to prevent or solve crime by using low cost web camera or high end camera (11) of better resolution. Using the concept of "motion detection by vision" to achieve motion detection capability, no hardware sensors are required. Therefore, this intelligent motion detection capability may assist in reducing monitoring manpower and allow the systems to utilize a low cost web camera (11). The program has an easy to operate parameter setting, where a user can adjust the parameters according to individual requirement, to detect the motion video image. Hence, the present invention has a user friendly program and easy do-it-yourself video surveillance and security systems.